2009
DOI: 10.3174/ajnr.a1688
|View full text |Cite
|
Sign up to set email alerts
|

Pseudopathologic Brain Parenchymal Enhancement due to Venous Reflux from Left-Sided Injection and Brachiocephalic Vein Narrowing

Abstract: SUMMARY:In this report, we present a case of a patient with CT angiographic artifacts related to left-sided venous injection resulting in a striking pattern of enhancement simulating vascular abnormalities, which prompted additional diagnostic imaging. To our knowledge, no similar case has been reported in the published literature to date. With the development of high-speed multidetector CT units, CT angiography is increasingly becoming a primary tool for evaluation of the vasculature of the head and neck. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…The reflux of contrast till the level of dural venous sinuses is a rare phenomenon and on reviewing previous literature, we found only one case report by Chen et al 9 Similar finding by using magnetic resonance angiography (MRA) was reported by Paksoy et al 7 who attributed reflux to brachiocephalic venous stenosis.…”
Section: Figsupporting
confidence: 79%
“…The reflux of contrast till the level of dural venous sinuses is a rare phenomenon and on reviewing previous literature, we found only one case report by Chen et al 9 Similar finding by using magnetic resonance angiography (MRA) was reported by Paksoy et al 7 who attributed reflux to brachiocephalic venous stenosis.…”
Section: Figsupporting
confidence: 79%
“…incidental finding in asymptomatic patients, and mainly related to venous compression, development of collateral vessels, and incompetent venous valves. 1,2…”
mentioning
confidence: 99%
“…1 Left-sided injections are proposed to predispose to venous reflux due to anatomic variations between the left and right brachiocephalic veins. 9 The left brachiocephalic vein crosses the aorta and is more susceptible to anatomic compression due to the relatively narrow retrosternal space through which it courses, whereas the right brachiocephalic vein takes a more direct course more distant from the potential compressive effects of the aorta and sternum.…”
Section: In Selected Dsc-mr Perfusion Source Images At Zero Seconds mentioning
confidence: 99%